2014
DOI: 10.1259/bjr.20130753
|View full text |Cite
|
Sign up to set email alerts
|

An arranged marriage for precision medicine: hypoxia and genomic assays in localized prostate cancer radiotherapy

Abstract: Prostate cancer (CaP) is the most commonly diagnosed malignancy in males in the Western world with one in six males diagnosed in their lifetime. Current clinical prognostication groupings use pathologic Gleason score, pre-treatment prostatic-specific antigen and Union for International Cancer Control-TNM staging to place patients with localized CaP into low-, intermediate-and high-risk categories. These categories represent an increasing risk of biochemical failure and CaP-specific mortality rates, they also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 97 publications
0
31
0
1
Order By: Relevance
“…There has been an increasing interest in evaluating the hypoxic status in various tissue sites, as for example in prostate cancer [24,25]. A previous study aiming at evaluating the 15-gene hypoxia classifier in patients with loco-regional gastroesophageal cancer did not give a clear answer of the applicability [26].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing interest in evaluating the hypoxic status in various tissue sites, as for example in prostate cancer [24,25]. A previous study aiming at evaluating the 15-gene hypoxia classifier in patients with loco-regional gastroesophageal cancer did not give a clear answer of the applicability [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in primary tumours have, however, identified genomic instability as a driver of disease aggressiveness and treatment failure in both surgical and radiation treatment of prostate cancer. [137][138][139] Furthermore, it appears that patient-specific measurements of tumour hypoxia and genomic instability provide complementary information about clinical outcome, with hypoxia being more or less important in some genomic subgroups than in others, 138 emphasizing the role of the tumour microenvironment.…”
Section: Future Studiesmentioning
confidence: 99%
“…Oxygen concentration below 10 mm Hg increases the expression of HIF-1 factor and activates many other molecular pathways which ensure the maintenance of basic cellular functions. This complex and dynamic response has massive implications such as increased angiogenesis, transition from aerobic to anaerobic metabolism, the inhibition of apoptosis and activation of growth factors as well as irreversible changes in cell genome [12][13][14].…”
Section: Hypoxia In a Tumourmentioning
confidence: 99%